Determinants of maternal, infant, and young child nutrition during the 1,000-day window of opportunity in Solomon Islands: A focused ethnographic study - Grey, Kelsey; Kodish, Stephen R.; Namohunu, Salome Aroma; Losi, Jill; Matean, Maryam; Palaniappan, Uma; Northrup-Lyons, Martina; Cherian, Arlin; Gwavuya, Stanley; McLean, Judy; Erasmus, Wendy (Frontiers in Nutrition, 2023)
This focused ethnographic study used qualitative, ethnographic, and participatory methods to explore determinants of maternal, infant, and young child nutrition (MIYCN) during the first 1,000 days of life as part of efforts to address the double burden of malnutrition in Solomon Islands. An iterative study design was used to first explore and then confirm findings related to food and nutrition security and social and behavioural determinants of MIYCN in urban and rural settings. The first phase included in-depth interviews, household observations, free lists, and seasonal food availability calendar workshops while the second phase included focus group discussions, pile sorts, participatory community workshops, and repeated household observations. We found that MIYCN is shaped by a complex interaction of factors at the macro- and micro-levels. At the macro-level, globalization of the food system, a shifting economy, and climate change are driving a shift towards a delocalized food system based on imported processed foods. This shift has contributed to a food environment that leaves Solomon Islanders vulnerable to food and nutrition insecurity, which we found to be the primary determinant of MIYCN in this context. At the micro-level, this food environment leads to household- and individual-level food decisions that often do not support adequate MIYCN. Multi-sectoral interventions that address the macro- and micro-level factors shaping this nutrition situation may help to improve MIYCN in Solomon Islands.